‘THE RULE OF THREE’ IN THE GROWTH STORIES – GANGBAIK LEE’S DRAMA “LIKE LOOKING AT THE FLOWER IN THE MIDWINTER” - KIM, Mansu (International Journal of Korean Humanities and Social Sciences, 2016)
This paper focused on the structure of the growth stories, especially in surveying Gangbaek Lee’s (이강백) drama “Like Looking at the Flower in the Mid-winter (동지섣달 꽃 본 듯이)”. It is structured by ‘rule of the three’. In this text, three sons go to seek their mother, they experience the tests three times. Third son wins the game because he succeeds to find his true and alternative mother. It is similar to the story of English fairy tale “Three Little Pigs”. In Freudian terms, the characters of the both texts are superego, ego and id. The core of the growth story is that third son (id) wins the first son (superego) and the second son (ego) by using his own energy (meaningful labor). In Levi Strauss’ terms, the contrast between the third and the others can be schemed the contrast between culture and nature. Lee’s drama presents the third son as the real hero who overcomes two elder brothers. The first is so conservative (oversleep), the second is so selfish (overeat). Two brothers were too political or too ideal to become a true, humanistic and warm-minded adult. In his view, ‘drama’ related to the third son is the most humanistic and warm-minded action in the world. These both stories are based on the plot ‘rags to riches’ which contains the success of the poor and powerless. In other words, the poor and weak child can grow to the true hero, and reach the final destination, according to the Gustav Jung’s expression, ‘the Self as a Whole’.